2014
DOI: 10.1186/1746-1596-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of both platelet-derived growth factor-BB and vascular endothelial growth factor-C and its association with lymphangiogenesis in primary human non-small cell lung cancer

Abstract: BackgroundMetastatic spread of tumor through lymphatic vasculature is an important adverse prognostic factor in a variety of human cancer and tumor lymphangiogenesis requires the interplay of several growth factors. Platelet-derived growth factor (PDGF)-BB and vascular endothelial growth factor (VEGF)-C are two important molecules involving in tumor metastasis and lymphangiogenesis. Therefore, the aim of this study was to investigate the coexpression of PDGF-BB and VEGF-C in primary human non-small cell lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…VEGFC and platelet-derived growth factor BB (PDGF-BB) have been extensively studied in lymphangiogenesis [94,95]. VEGFC and PDGF-BB co-expression is also related to lymphangiogenesis in lung cancer [96]. The results above suggest that both the VEGFC/NFAT1 and PDGF/ NFAT1 pathways are involved in tumor lymphangiogenesis.…”
Section: Nfats In Tumor Angiogenesis and Lymphangiogenesismentioning
confidence: 84%
“…VEGFC and platelet-derived growth factor BB (PDGF-BB) have been extensively studied in lymphangiogenesis [94,95]. VEGFC and PDGF-BB co-expression is also related to lymphangiogenesis in lung cancer [96]. The results above suggest that both the VEGFC/NFAT1 and PDGF/ NFAT1 pathways are involved in tumor lymphangiogenesis.…”
Section: Nfats In Tumor Angiogenesis and Lymphangiogenesismentioning
confidence: 84%
“…The expression of PDGFRa/b and PDGF-A/B in NSCLC is associated with poor prognosis (170)(171)(172). PDGF signaling is important for tumor growth, angiogenesis, and lymphangiogenesis in vivo; this was affected by coexpression of PDGF-BB and VEGF-C (or VEGFR3) in NSCLC, also resulting in poor prognosis (172)(173)(174). The angiogenic properties of PDGF ligands are supported by the finding that PDGF-AA regulates VEGF expression in an autocrine way and facilitates the malignant process of transforming precancerous lesions to advanced cancer (175).…”
Section: Pdgf Signaling In Lung Diseasementioning
confidence: 98%
“…Non‐small cell lung cancer (NSCLC) patients who had overexpression of both PDGF‐BB and VEGF‐C presented with higher tumour growth and lymphatic invasion . Crenolanib has been shown to be effective against PDGFR and induced apoptosis in NSCLC A549 cells.…”
Section: Introductionmentioning
confidence: 97%
“…However, T β RII endocytosis and SMAD2 phosphorylation were not noted in PDGFR α ‐silenced cells. Human colorectal cancer HT29 cells were implanted into the liver of severe combined immunodeficiency mice, and results revealed that HT29 cells colonization in the liver induced activation of HSCs as evidenced by upregulated expression of PDGFR α in HSCs …”
Section: Introductionmentioning
confidence: 99%